Use of spineless cactus associated with legume hay in the feedlot-finishing of lambs in semi-arid regions. - Maria Gabriela da Trindade Silva; Marcone Geraldo Costa; Mariana Campelo Medeiros; Gelson Dos Santos Difante; Paulo Sérgio de Azevedo; Antonio Leandro Chaves Gurgel; João Virgínio Emerenciano Neto; Emmanuel Liévio de Lima Veras; Luís Carlos Vinhas Ítavo (PLoS ONE)
The objective of this study were to examine the effects of diets containing spineless cactus associated with hays of different legume species [gliricidia (Gliricidia sepium), "catingueira" (Caesalpinia bracteosa), "sabiá" (Mimosa caesalpiniifolia Benth) and "catanduva" (Piptadenia moniliformis Benth)] on the intake, digestibility, performance and carcass traits of lambs. Twenty-four ½ Santa Inês × ½ Soinga lambs with an average body weight of 21.4 ± 2.53 kg were distributed into four treatments in a completely randomized design. Treatments consisted of diets formulated with the association of spineless cactus (Opuntia ficus-indica Mill) and hay of four legume species, namely, "catanduva", "sabiá" "catingueira" and gliricidia. The lowest intakes (P<0.05) of dry matter (DM), organic matter (OM), neutral detergent fiber (NDF) and total carbohydrates occurred in the animals that received the diet containing catingueira hay. However, there were no diet effects (P>0.05) on the intakes of crude protein (CP), ether extract and non-fibrous carbohydrates. The diets also did not change (P>0.05) the weight gain (0.197 kg/day) or final weight (33.18 kg) of the lambs or the apparent digestibility coefficients of DM, OM, CP and NDF. Consequently, the parameters of live weight at slaughter (34.10 kg), hot carcass weight (14.81 kg), cold carcass weight (14.66 kg), hot carcass yield (45.60%) and cold carcass yield (45.07%) exhibited the no response to treatment. In addition to these variables, the diets also did not influence subcutaneous fat thickness (2.54 mm), longissimus muscle area (13.34 cm2), morphometric measurements of the carcass, or the proportions of muscle and fat. Therefore, legume hays associated with spineless cactus can be used to feed ½ Santa Inês × ½ Soinga lambs in the feedlot, as this strategy provides heavy animals at the time of slaughter and carcasses with desirable degrees of muscularity and adiposity.